The Risk of Developing Tinnitus and Air Pollution Exposure - Lai, Po-Yu; Lee, Chang-Yin; Chang, Kuang-Hsi; Chang, Yu-Kang; Hsu, Yi-Chao; Chiu, Ing-Ming; Tsai, Stella Chin-Shaw; Cho, Der-Yang; Lin, Cheng-Li; Lin, Tsung-Hsing; Chuang, Wu-Lung (Atmosphere, 2025)
(1) Background: The role of air pollutants as risk factors for tinnitus remains unclear. To address this gap in research, we conducted a nationwide retrospective cohort study in Taiwan by integrating patients’ clinical data with daily air quality data to evaluate the environmental risk factors associated with tinnitus. (2) Methods: The Taiwan National Health Research Database (NHIRD) includes medical records for nearly all residents of Taiwan. To assess pollution levels, we used daily air quality data from the Taiwan Environmental Protection Agency regarding SO2, CO, NO, NOX, and particulate matter (PM2.5 and PM10). We merged the NHIRD data with air quality information based on the residents’ locations and the positions of air quality monitoring stations. Pollutant levels were then categorized into quartiles (Q1, Q2, Q3, and Q4). (3) Results: This study included 284,318 subjects. After controlling for covariates, the adjusted HR (95 CI%) for tinnitus increased with increasing SO2, CO, NO, NOX, PM2.5, and PM10 exposure levels, specifically from 1.24 (95 CI% = 1.18, 1.30) to 1.35 (95 CI% = 1.28–1.41); from 1.15 (95 CI% = 1.09, 1.21) to 1.90 (95 CI% = 1.81, 2.00); from 0.86 (95 CI% = 0.82, 0.91) to 1.69 (95 CI% = 1.62, 1.77); from 1.62 (95 CI% = 1.54, 1.71) to 1.69 (95 CI% = 1.60, 1.77); from 0.16 (95 CI% = 0.15, 0.18) to 2.70 (95 CI% = 2.57, 2.84); and from 2.53 (95 CI% = 2.38, 2.69) to 3.58 (95 CI% = 3.39, 3.78), respectively, compared to the Q1 concentrations for all air pollutants. (4) Conclusions: During the 15-year follow-up period, we found a significant positive correlation between air pollutant exposure and the risk of tinnitus.